Structure and molecular mobility of soy glycinin in the solid state - Kealley, Cat; Rout, M.; Dezfouli, M.; Strounina, E.; Whittaker, A.; Appelqvist, I.; Lillford, P.; Gilbert, E.; Gidley, M. (American Chemical Society, 2008)
We report a multitechnique study of structural organization and molecular mobility for soy glycinin at a low moisture content (<30% w/ w) and relate these to its glass-to-rubber transition. Small-angle X-ray scattering (SAXS), differential scanning calorimetry (DSC), Fourier transfortn infrared (FTIR) spectroscopy, and nuclear magnetic resonance (NMR) spectroscopy are used to probe structure and mobility on different length and time scales. NMR (~10-6 to 10-3 s) reveals transitions at a higher moisture content (> 17%) than DSC or SAXS, which sample for much longer times (~10 to 103 s) and where changes are detected at > 13% water content at 20 °C. The mobility transitions are accompanied by small changes in unit-cell parameters and IR band intensities and are associated with the enhanced motion of the polypeptide backbone. This study shows how characteristic features of the ordered regions of the protein (probed by SAXS and FTIR) and mobile segments (probed by NMR and DSC) can be separately monitored and integrated within a mobility transformation framework. © 2008 American Chemical Society.